Competitive running at high altitude: Is it safe? - Roi, G. S.; Giacometti, M.; Banfi, G.; Zaccaria, M.; Gritti, I.; von Duvillard, S. P. (Medicine & Science in Sports & Exercise, 1999)
Athletes (N = 1,442) participating in 36 competitions at altitudes between 2,000 and 5,200 m since 1991, were screened by a physician and had blood samples taken. Those allowed to compete were healthy, altitude acclimatized, well trained, and without a history of altitude-related health problems. Racing at altitude did produce some temporary changes in physiology but the most were similar to those exhibited at low altitude. Implication: Competitive running at high altitude does not impose a substantial increase in health risk beyond that encountered at low altitude provided participating athletes are well-trained, altitude acclimatized, and medically controlled.